Context, implementation and mechanisms of impact of a stepped-care WHO psychological intervention for migrants with psychological distress - Beatrice Compri; Giulia Turrini; Marianna Purgato; Richard Bryant; Paula Cristobal; Josep Maria Haro; Raffael Kalisch; Vincent Lorant; David McDaid; Kerry R. McGreevy; Roberto Mediavilla; Michela Nosè; et al. (Cambridge Prisms: Global Mental Health)
Migrants often experience psychological distress due to pre-, peri- and post-migration stressors. Scalable interventions like Doing What Matters in Times of Stress (DWM) and Problem Management Plus (PM+) have been developed to address these challenges. This study evaluates a stepped-care program combining DWM and PM+ for migrants in Italy, examining its context, implementation, and mechanisms of impact. A mixed-methods process evaluation was conducted alongside a randomized controlled trial (RCT), following the Medical Research Council (MRC) framework. Post-trial qualitative data were collected through individual interviews with intervention participants (n = 10) and stakeholders (n = 10), as well as a focus group with intervention providers (n = 8). Thematic analysis was performed using NVivo. Cultural stigma and practical barriers influenced engagement, while community leaders fostered trust and participation. Interventions were feasible and acceptable. Digital delivery improved accessibility for some but posed challenges for those with low technological literacy or private spaces. The stepped-care approach supported gradual engagement with mental health strategies, enhancing self-care and emotional awareness, while provider relationships were key to sustaining motivation. The stepped-care model alleviated psychological distress and was well-received. Findings underscore the need for cultural sensitivity, digital accessibility and community engagement to optimize migrant mental health support.